SMG603 : Tourism planning management / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2023)
This course aims to familiarize students with the planning, operations and marketing tourism activity. It provides holistic and rigorous examination of the key issues of tourism development. It will address the nature of tourism and tourists’ awareness of the economic, social and environmental issues that can result from their activity and also managing tourism research survey as part of the process.